Deletion of Wiskott–Aldrich syndrome protein triggers Rac2 activity and increased cross-presentation by dendritic cells - Marisa A. P. Baptista (Nature Portfolio, 2016)
Wiskott–Aldrich syndrome (WAS) is a severe X-linked primary immunodeficiency syndrome. Here, the authors show that loss of WAS gene in dendritic cells results in increased activity of Rac2, increase of phagosomal pH, and more efficient cross-presentation.